Implementasi Kebijakan Penggunaan Sosial Media dalam Komunikasi Antara Sekolah dengan Wali Murid : Studi di Sekolah Dasar Negeri 4 Masbagik Timur Tahun 2024 - Yuniar Affandy; Salmi Yuniar Bahri; Mardiana Mardiana; Muhammad Atha' Iqbal (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The background of this study is the importance of effective communication between schools and parents in supporting the education process and student development. Social media has become one of the popular and effective communication tools in conveying information quickly and widely. This study aims to determine the implementation of social media use policies in communication between schools and parents and supporting and inhibiting factors. The research method used is a qualitative approach with documentation techniques, observation and in-depth interviews with schools and parents. The results of the study show that the use of social media has provided many benefits in increasing the speed and efficiency of communication between schools and parents. However, there are several obstacles such as lack of response from some parents, limited internet access, and limited technological infrastructure. However, support from adequate technological infrastructure and active participation from parents can be the main supporting factors in the successful implementation of this policy.